Strategic Responses to Standardization: Embrace, Extend or Extinguish? - WOODARD, C. Jason (Institutional Knowledge at Singapore Management University, 2011)
Prior research on technology standardization has focused on two common patterns: processes in which product developers and other stakeholders cooperate to achieve a consensus outcome, and “standards wars” in which competing technologies vie for dominance in the market. This study examines Microsoft's responses to 12 software technologies in the period between 1990 and 2005. Despite the company's reputed tendency to pursue a strategy dubbed “embrace, extend, and extinguish,” a content analysis of news articles from the same period reveals surprising diversity in Microsoft's responses at the product level. We classify these responses using a typology that treats “embrace” and “extend” as orthogonal decisions faced by product development organizations. This typology allows four kinds of outcomes to be distinguished, including two kinds of partial compatibility in addition to the familiar cases of full compatibility and incompatibility. To complement this cross-sectional perspective, we examine more closely the evolution of Microsoft's strategy with respect to Sun's Java technology. This longitudinal view highlights another underappreciated aspect of standardization, namely the extent to which a firm's strategic posture toward a standard can change over time, even within the same product family. Based on this evidence, we suggest that firms tend to publicly embrace a standard with the aim of gaining legitimacy with a community of adopters, whereas efforts to extend a standard tend to be motivated by the intent to leverage the underlying technology to achieve or strengthen architectural control. We argue that legitimacy and leverage are strategic complements, making the “embrace and extend” strategy attractive to firms like Microsoft, but that the resulting outcome is unstable. Firms that pursue this strategy ultimately face a choice between contributing their extensions back to the standard and losing proprietary leverage, or giving up the legitimacy associated with standards compliance in exchange for freedom from the constraints of compatibility.